Poverty and Income Distribution - David Jesuit; Timothy Smeeding (Luxembourg Income Study (LIS), 2002)
This paper provides a brief overview of the basic concepts and measures used to estimate income inequality and poverty in the developed world. A summary assessment of the available comparative databases is included in our discussion. We also examine the relative merits of absolute and relative measures of poverty in detail and review alternative measures of income inequality. Finally, we present the most recent figures on income inequality and poverty, including for children and the elderly, for twenty-two countries using data from the Luxembourg Income Study.
Keywords: 330; Armut; Einkommensverteilung; Vergleich; Welt